USULAN MODEL PERKULIAHAN KURIKULUM INDUSTRI 4.0 DENGAN PENDEKATAN SIKLUS MANUFAKTUR DAN PROSES BISNIS DI POLITEKNIK ATI PADANG - Zulhamidi Zulhamidi (Politeknik ATI Padang, 2019)
In 2018, the Ministry of Industry initiate the Making Indonesia 4.0 program in response to rapidly increasing of information technology and the internet growth. This initiative followed by the Regulation of the Minister of Industry No. 1532 about the Industri 4.0 curricula. Polytechnic ATI Padang as a Vocational College of the Ministry of Industry that the job and function is to produce skilled labour that able to prepare these challenges in the term of appropriate curricula and lectures book. This paper tries to analyze the existing condition of the Polytechnic ATI Padang and the technical implementation of lectures in accordance with the Curriculum 4.0 policy implemented by the government. The proposed model is a reviewed of 9 (nine) pillars of technology in Industry 4.0 which combined to the academic document and the manufacturing cycle model in industrial business processes.